Soluble organic matter removal in wastewater containing chromium (III) by polyaluminium chloride with high Al13 content - Shaik Muhammad Hasbullah Shaik Ismail, 1988-; Wan Azlina Ahmad, supervisor; Zainul Akmar Zakaria, supervisor; Fakulti Sains (2010)
Preoject paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010